The up-to-date Features of the Arbores Poetry in the Conditions of Diculturalism and Diglosia - HimÃ§i, Denis (Mediterranean Journal of Social Sciences, 2012)
In the 19th century, in the Arbores of Italy locations, an Albanian literature was developed, which for its famous content andartistic values, is part of a brilliant page of the history of literature and in general of the Albanian National Renaissance, where in the lasttwo to three decades, with pleasure we notice a rebirth of the tradition of literature known like its second â€œrenaissanceâ€. From theselocations we have had not only local singers and poets (known in the local Arbores communities) but as well but as well in the entireliterature world in Italy and Europe. Throughout an analysis and interpretation in this article, I will reveal the tendency towards theelevation of the written language level with all its functions, making attempts to be incorporate a new lexical fund as well, characteristicfor the nowadays world. This article will serve to highlight the issues of the Albanian language only, an issue that is situated historicallyfrom the specific circumstances of the Albanians, and of Diaspora as well, desiring to reinforce their connections to the trunk, they shouldfollow the linguistic trunk model.